Age and gender disparities in oral anticoagulant use: a nine-year nationwide drug utilization analysis - Omer, Ahmed A. A.; Csatordai, Márta; Viola, Réka; Doró, Péter (Frontiers in Pharmacology, 2026)
BackgroundCardiovascular diseases remain the leading cause of mortality in Europe, responsible for one-third of all deaths in 2021. In Hungary, the standardized death rate from cardiovascular diseases reached 722.8 per 100,000 individuals, more than double the EU average. Oral anticoagulants (OACs) play a crucial role in lowering cardiovascular mortality. The use of OACs has shifted rapidly over the past decade with the transition from vitamin K antagonists (VKAs) to direct oral anticoagulants (DOACs). Although previous studies have examined gender differences in OACs prescribing, most rely on patient-level registries and do not capture population-level exposure.AimTo evaluate population-level trends in OACs consumption in Hungary from 2014 to 2022, stratified by age and gender, with a specific focus on detecting temporal changes in the gender gap.MethodNational level data were obtained from the Hungarian National Health Insurance Fund database, which includes all reimbursed prescription medications for the entire population. Utilization was measured using the WHO’s ATC/DDD methodology and expressed as defined daily doses per 1,000 inhabitants per day (DID). Linear regression was used to assess trends.ResultsTotal OACs use nearly doubled over the study period, increasing from 9.79 to 18.73 DID (Coeff. = 1.18, p < 0.001). VKAs use declined significantly in both genders by 41.2% in males and 47.8% in females, while DOACs use increased more than tenfold. OACs utilization was consistently higher in males. Gender differences in DOACs, initially negligible, began to widen from 2018 onward, whereas, VKAs utilization exhibited a consistently wider gender difference across all years. OACs use increased with age, peaking in the 80–84 age group. Apixaban became the most used OAC, reaching 6.11 DID in 2022.ConclusionA marked shift from VKAs to DOACs occurred, with overall OACs use nearly doubling, with a widening gender gap in consumption of both VKAs and DOACs. Utilization was consistently higher among males and increased with age, highlighting the importance of continued monitoring to ensure effective and evidence-based anticoagulant use.